2002
DOI: 10.4049/jimmunol.169.11.6594
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing In Vivo Immunoglobulin Class Switch DNA Recombination in Chronic Lymphocytic Leukemia B Cells

Abstract: Chronic lymphocytic leukemia (CLL) results from the expansion of malignant CD5+ B cells that usually express IgD and IgM. These leukemic cells can give rise in vivo to clonally related IgG+ or IgA+ elements. The requirements and modalities of this process remain elusive. Here we show that leukemic B cells from 14 of 20 CLLs contain the hallmarks of ongoing Ig class switch DNA recombination (CSR), including extrachromosomal switch circular DNAs and circle transcripts generated by direct Sμ→Sγ, Sμ→Sα, and Sμ→Sε … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 82 publications
6
76
0
2
Order By: Relevance
“…Our results provide evidences that high expression of AID mRNA and ASHM are associated with the development of RT and PLT in CLL patients. In line with previous reports, 17,18 all CLLs analyzed in this study expressed AID mRNA at various levels but the expression levels remained well below that of normal GC B-cells. Chronic lymphocytic leukemia cases that showed no transformation and cases that eventually transformed to higher-grade lymphoma expressed AID at similar levels.…”
Section: Discussionsupporting
confidence: 76%
“…Our results provide evidences that high expression of AID mRNA and ASHM are associated with the development of RT and PLT in CLL patients. In line with previous reports, 17,18 all CLLs analyzed in this study expressed AID mRNA at various levels but the expression levels remained well below that of normal GC B-cells. Chronic lymphocytic leukemia cases that showed no transformation and cases that eventually transformed to higher-grade lymphoma expressed AID at similar levels.…”
Section: Discussionsupporting
confidence: 76%
“…26,29 One could speculate that the association of AID with deletion in 11q (frequently observed in nodal CLL) and CD38 expression is somehow related to the pattern of CD19 þ / CD38 þ /IgD À germinal centre cells. 34 The majority of unmutated cases were AID-positive, but even 47% of mutated cases still expressed AID.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Activation-induced cytidine deaminase (AID) is normally expressed in CD19 þ /CD38 þ germinal centre B-cells and essential for somatic hypermutation, suggesting its potential association with IGV H mutational status. [25][26][27][28][29] Indeed, two reports have recently described the expression of AID in unmutated B-CLL cases. 28,30 However, a third study found no association between AID expression and IGV H mutation status.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence supports the concept that intraclonal CLL cell diversity plays a role in the disease biology and eventual clinical outcome (11)(12)(13). Intraclonal heterogeneity is acquired through spontaneous genetic alterations or driven by microenvironmental stimuli (14,15). Recently, CLL cells expressing CD38 were shown to be a proliferating subset, as they strongly express Ki-67 and have a faster proliferation rate in vivo than do CD38 2 CLL cells of the same clone (13).…”
mentioning
confidence: 92%